Detection of the secondary, low‐affinity β1‐adrenoceptor site in living cells using the fluorescent CGP 12177 derivative BODIPY‐TMR‐CGP. (December 2014) - Gherbi, K; Briddon, S J; Hill, S J
<x xml:space="preserve">Abstract</x> Background and Purpose CGP 12177 not only inhibits agonist effects mediated through the catecholamine site of the β1‐adrenoceptor with high affinity, but also exhibits agonist effects of its own at higher concentrations through a secondary, low‐affinity β1‐adrenoceptor site or conformation. β‐blocker affinities for this 'CGP 12177' site of the human β1‐adrenoceptor have thus far only been characterized in functional studies. Here, we used the fluorescent CGP 12177 analogue BODIPY‐TMR‐CGP to directly investigate receptor–ligand interactions at the secondary binding site of the β1‐adrenoceptor. Experimental Approach The human β1‐adrenoceptor was stably expressed in CHO cells containing a cAMP response element (CRE)‐secreted placental alkaline phosphatase (SPAP) reporter gene construct. Functional responses of BODIPY‐TMR‐CGP were determined in the CRE‐SPAP reporter gene assay, and manual and automated confocal microscopy platforms used to investigate the binding properties of BODIPY‐TMR‐CGP. Key Results BODIPY‐TMR‐CGP displayed a pharmacological profile similar to that of CGP 12177, retaining agonist activity at the secondary β1‐adrenoceptor site. In confocal microscopy studies, specific BODIPY‐TMR‐CGP binding allowed clear visualization of β1‐adrenoceptors in live cells. Using a wider concentration range of labelled ligand in a high‐content fluorescence‐based binding assay than is possible in radioligand binding assays, two‐site inhibition binding curves of β‐adrenoceptor antagonists were revealed in CHO cells expressing the human β1‐adrenoceptor, but not the β2‐adrenoceptor. Conclusions and Implications The fluorescent CGP 12177 analogue allowed the detection of the β1‐adrenoceptor secondary site in both functional and binding studies. This suggests that BODIPY‐TMR‐CGP presents an important and novel fluorescent tool to investigate the nature of the secondary β1‐adrenoceptor site.